Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of the differences between biofilm and planktonic Brucella abortus via metabolomics and proteomics - Taishan Tang; Ye Xu; Jianfeng Wang; Xiao Tan; Xiaona Zhao; Ping Zhou; Fande Kong; Changqing Zhu; Chengping Lu; Huixing Lin (Functional & Integrative Genomics, 2021)

Analysis of brain metabolites by gas chromatography–mass spectrometry reveals the risk–benefit concerns of prednisone in MRL/lpr lupus mice - Jia Zhou; Feilong Lu; Shan Li; Meijuan Xie; Haimei Lu; Zhijun Xie; Dehong Wu; Shuang Wang; Chengping Wen; Zheng-Hao Xu (Inflammopharmacology, 2020)

Limited preventive effect of prednisone on neuropsychiatric symptoms in murine systemic lupus erythematosus - Feilong Lu; Haimei Lu; Meijuan Xie; Shan Li; Yunyun Zu; Jia Zhou; Jie Yu; Shuang Wang; Yeping Ruan; Chengping Wen; Zhenghao Xu (Inflammopharmacology, 2019)

Correction to: Oral prednisolone versus non-steroidal anti-inflammatory drugs in the treatment of acute gout: a meta-analysis of randomized controlled trials - Jie Yu; Haimei Lu; Jia Zhou; Zhijun Xie; Chengping Wen; Zhenghao Xu (Inflammopharmacology, 2019)

Oral prednisolone versus non-steroidal anti-inflammatory drugs in the treatment of acute gout: a meta-analysis of randomized controlled trials - Jie Yu; Haimei Lu; Jia Zhou; Zhijun Xie; Chengping Wen; Zhenghao Xu (Inflammopharmacology, 2018)

Identification and Detection of Serotype-Specific Genes: Effective Serotyping of Streptococcus suis - Kaicheng Wang; Zongfu Wu; Huochun Yao; Yuan Qiu; Chengping Lu (Current Clinical Microbiology Reports, 2017)

Mac Protein is not an Essential Virulence Factor for the Virulent Reference Strain Streptococcus suis P1/7 - Genhui Xiao; Zongfu Wu; Shouming Zhang; Huanyu Tang; Fengqiu Wang; Chengping Lu (Current Microbiology, 2017)

PAAR‐Rhs proteins harbor various C‐terminal toxins to diversify the antibacterial pathways of type VI secretion systems - Jiale Ma; Min Sun; Wenyang Dong; Zihao Pan; Chengping Lu; Huochun Yao (Environmental Microbiology, 2017)
Summary The type VI secretion system (T6SS) of bacteria plays a key role in competing for specific niches by the contact‐dependent killing of competitors. Recently, Rhs proteins with polymorphic C‐terminal toxin‐domains that inhibit or kill neighboring cells were identified. In this report, we identified a novel Rhs with an MPTase4 (Metallopeptidase‐4) domain (designated as Rhs‐CT1) that showed an antibacterial effect via T6SS in Escherichia coli . We managed to develop a specific strategy by matching the diagnostic domain‐architecture of Rhs‐CT1 (Rhs with an N‐terminal PAAR‐motif and a C‐terminal toxin domain) for effector retrieval and discovered a series of Rhs‐CTs in E. coli . Indeed, the screened Rhs‐CT3 with a REase‐3 (Restriction endonuclease‐3) domain also mediated interbacterial antagonism. Further analysis revealed that vgrG O1 and eagR/DUF1795 (upstream of rhs‐ct ) were required for the delivery of Rhs‐CTs, suggesting eagR as a potential T6SS chaperone. In addition to chaperoned Rhs‐CTs, neighborless Rhs‐CTs could be classified into a distinct family (Rhs‐Nb) sharing close evolutionary relationship with T6SS2‐Rhs (encoded in the T6SS2 cluster of E. coli ). Notably, the Rhs‐Nb‐CT5 was confirmed bioinformatically and experimentally to mediate interbacterial antagonism via Hcp2B‐VgrG2 module. In a further retrieval analysis, we discovered various toxin/immunity pairs in extensive bacterial species that could be systematically classified into eight referential clans, suggesting that Rhs‐CTs greatly diversify the antibacterial pathways of T6SS.

Characterization and complete genome sequence analysis of Staphylococcus aureus bacteriophage JS01 - Hongying Jia; Wenyang Dong; Lvfeng Yuan; Jiale Ma; Qinqin Bai; Zihao Pan; Chengping Lu; Huochun Yao (Virus Genes, 2015)

Fifteen novel immunoreactive proteins of Chinese virulent Haemophilus parasuis serotype 5 verified by an immunoproteomic assay - Yanfei Yu; Guangyan Wu; Zhipeng Zhai; Huochun Yao; Chengping Lu; Wei Zhang (Folia Microbiologica, 2015)

The Truncated Major Pilin Subunit Sbp2 of the srtBCD Pilus Cluster Still Contributes to Streptococcus suis Pathogenesis in the Absence of Pilus Shaft - Jing Shao; Wei Zhang; Zongfu Wu; Chengping Lu (Current Microbiology, 2014)

Biofilm Formation, Host-Cell Adherence, and Virulence Genes Regulation of Streptococcus suis in Response to Autoinducer-2 Signaling - Yang Wang; Li Yi; Zhicheng Zhang; Hongjie Fan; Xiangchao Cheng; Chengping Lu (Current Microbiology, 2014)

Characterization and genome sequencing of a novel bacteriophage infecting Streptococcus agalactiae with high similarity to a phage from Streptococcus pyogenes - Qinqin Bai; Wei Zhang; Yongchun Yang; Fang Tang; Xuanhoa Nguyen; Guangjin Liu; Chengping Lu (Archives of Virology, 2013)

Characterization of Streptococcus suis Isolates from Slaughter Swine - Kaicheng Wang; Wei Zhang; Xiaocheng Li; Chengping Lu; Jiming Chen; Weixing Fan; Baoxu Huang (Current Microbiology, 2013)

Protection of guinea pigs by vaccination with a recombinant swinepox virus co-expressing HA1 genes of swine H1N1 and H3N2 influenza viruses - Jiarong Xu; Deji Yang; Dongyan Huang; Jiaping Xu; Shichao Liu; Huixing Lin; Haodan Zhu; Bao Liu; Chengping Lu (Archives of Virology, 2013)

Analysis of synonymous codon usage patterns in torque teno sus virus 1 (TTSuV1) - Zhicheng Zhang; Wei Dai; Yang Wang; Chengping Lu; Hongjie Fan (Archives of Virology, 2013)

Development and evaluation of a dot blot assay for rapid determination of invasion-associated gene ibeA directly in fresh bacteria cultures of E. coli - Chunling Niu; Shaohui Wang; Chengping Lu (Folia Microbiologica, 2012)

Combined Antibacterial Activity of Phage Lytic Proteins Holin and Lysin from Streptococcus suis Bacteriophage SMP - Yibo Shi; Ning Li; Yaxian Yan; Hengan Wang; Yan Li; Chengping Lu; Jianhe Sun (Current Microbiology, 2012)

Mutations in the C-terminal tail of NS1 protein facilitate the replication of classical swine H1N1 influenza A virus in mice - Jinxiang Wang; Xian Qi; Chengping Lu (Folia Microbiologica, 2012)

Natural infection with torque teno sus virus 1 (TTSuV1) suppresses the immune response to porcine reproductive and respiratory syndrome virus (PRRSV) vaccination - Zhicheng Zhang; Yang Wang; Hongjie Fan; Chengping Lu (Archives of Virology, 2012)

Immunoproteomic assay of secreted proteins of Streptococcus suis serotype 9 with convalescent sera from pigs - Zongfu Wu; Wei Zhang; Jing Shao; Yang Wang; Yan Lu; Chengping Lu (Folia Microbiologica, 2011)

Hepatoprotective and antioxidant effects of Glycyrrhiza glabra extract against carbon tetrachloride (CCl4)-induced hepatocyte damage in common carp (Cyprinus carpio) - Guojun Yin; Liping Cao; Pao Xu; Galina Jeney; Miki Nakao; Chengping Lu (Fish Physiology and Biochemistry, 2011)

Molecular characterization of the 9.36 kb C-terminal region of canine coronavirus 1-71 strain - Guanggang Ma; Yuyan Wang; Chengping Lu (Virus Genes, 2008)